Use of PIM-funded research to guide Wellspring Advisors’ research agenda and funding priorities on cash transfers and intimate partner violence - CGIAR Research Program on Policies, Institutions, and Markets (2017)
PIM-funded IFPRI studies in Ecuador, Bangladesh, and Mali show impacts of cash transfer programs on intimate partner violence, in varying contexts and with varying design features. Wellspring Advisors, which develops grantmaking priorities and recommends grants to anonymous donors, supported two of these studies and closely engaged with researchers on findings. Wellspring has requested IFPRI researchers to advise how to move forward the research agenda and funding priorities on this topic, initiating discussions with a meeting in July 2018 at IFPRI.